Acquiring cybercrime evidence on mobile global positioning system (GPS): review - Abdullah, Nurul Azma; Mohd Rashid, Nurazidah (RAZI Publishing, 2017)
The use of Global Positioning System (GPS) as a device for finding directions is increasing from time to time. Within this growth, developers have taken a new inventiveness to apply this GPS system in a new environment. This new environment is called Internet of Thing (IoT) environment. This environment involves the device that connect to the internet such as smartphones and tablets. With this successful application, the mobile GPS has opened up a new space for forensic experts to get useful evidence in criminal cases. The connection between smartphone and GPS has raised the demand to examine the stored content of the devices. The stored content might include certain information such as home location, entered address or location, journey starts, ends and last GPS, call records and SMS. This critical data can be used in whole range of crime cases especially triage cases, for example, kidnapping cases, hit and run cases and many others.